Question
upstudy study bank question image url

1. In the first line, type the (implicit) function: \( x+y=3 \) 2. In the second line, type the (explicit) function \( (t)=-*)+5 \) 3. Celcutate (by hand) the intercepts for \( x+y=3 \). \[ \begin{array}{cc} x+0=3 & o+y=3 \\ x=3 & y=3 \end{array} \] The \( y \)-intercept(s) of \( x+y=3 \) is/are: \( (0,3) \) The \( x \)-intercept(s) of \( x+y=3 \) is/are: \( (3,0) \) Once you find the intercept(s) algebraically, confirm your intercepts using Desmos. 4. Calculate (by hand) the intercepts for \( f(x)=-x^{2}+5 \). The \( y \)-intercept(s) of \( f(x) \) is/are: The \( x \)-intercept(s) of \( f(x) \) is/are: Once you find the intercept(s) algebraically, confirm your intercepts using Desmos. 5. Calculate (by hand) the point(s) of intersection of the two graphs.

Ask by Pope Evans. in the United States
Feb 25,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

1. **Implicit Function**: \( x + y = 3 \) 2. **Explicit Function**: \( f(x) = -x^2 + 5 \) 3. **Intercepts for \( x + y = 3 \)**: - **y-intercept**: (0, 3) - **x-intercept**: (3, 0) 4. **Intercepts for \( f(x) = -x^2 + 5 \)**: - **y-intercept**: (0, 5) - **x-intercepts**: (√5, 0) and (–√5, 0) 5. **Intersection Points of the Two Graphs**: - (2, 1) - (–1, 4) Use Desmos to confirm these intercepts and intersection points.

Solution

Below is a step‐by‐step solution for the problem. ────────────────────────────── Step 1. Write the Implicit Function Write the equation in its given form:   x + y = 3 ────────────────────────────── Step 2. Write the Explicit Function The explicit function is given by:   f(x) = –x² + 5 ────────────────────────────── Step 3. Find the Intercepts for x + y = 3 • To find the y‐intercept, set x = 0:   0 + y = 3 ⟹ y = 3   The y‐intercept is: (0, 3) • To find the x‐intercept, set y = 0:   x + 0 = 3 ⟹ x = 3   The x‐intercept is: (3, 0) Confirm these intercepts using Desmos by graphing the equation x + y = 3. ────────────────────────────── Step 4. Find the Intercepts for f(x) = –x² + 5 • To find the y‐intercept, substitute x = 0:   f(0) = –(0)² + 5 = 5   The y‐intercept is: (0, 5) • To find the x‐intercepts, set f(x) = 0 and solve:   –x² + 5 = 0 ⟹ x² = 5 ⟹ x = ±√5   The x‐intercepts are: (√5, 0) and (–√5, 0) Again, you can confirm these intercepts on Desmos by graphing f(x) = –x² + 5. ────────────────────────────── Step 5. Find the Point(s) of Intersection of the Two Graphs The two equations are:   (1) x + y = 3   (2) y = –x² + 5 Use substitution. From (1), express y in terms of x:   y = 3 – x Replace in (2):   3 – x = –x² + 5 Solve for x:   –x² + 5 = 3 – x   Bring all terms to one side:   –x² + 5 – 3 + x = 0   –x² + x + 2 = 0 Multiply the entire equation by –1 to simplify:   x² – x – 2 = 0 Factor the quadratic:   (x – 2)(x + 1) = 0 Thus, the solutions for x are:   x = 2  or  x = –1 Find the corresponding y-values using y = 3 – x: • For x = 2:   y = 3 – 2 = 1   Intersection point: (2, 1) • For x = –1:   y = 3 – (–1) = 4   Intersection point: (–1, 4) Confirm these intersection points on Desmos by graphing both equations. ────────────────────────────── Summary of Answers 1. Implicit function:   x + y = 3 2. Explicit function:   f(x) = –x² + 5 3. Intercepts for x + y = 3:   y‐intercept: (0, 3)   x‐intercept: (3, 0) 4. Intercepts for f(x) = –x² + 5:   y‐intercept: (0, 5)   x‐intercepts: (√5, 0) and (–√5, 0) 5. Intersection points of the two graphs:   (2, 1) and (–1, 4) Use Desmos to verify these results by graphing the equations. Feel free to ask if you have any questions or need further explanation!

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

The Deep Dive

To find the intercepts for \( f(x)=-x^2+5 \), start with the \( y \)-intercept by evaluating \( f(0) \): \[ f(0) = -0^2 + 5 = 5. \] So the \( y \)-intercept is \( (0, 5) \). For \( x \)-intercepts, set \( f(x) = 0 \): \[ -x^2 + 5 = 0 \implies x^2 = 5 \implies x = \pm \sqrt{5}. \] Thus the \( x \)-intercepts are \( (\sqrt{5}, 0) \) and \( (-\sqrt{5}, 0) \). To find the intersection points of the two graphs, substitute \( y = 3 - x \) into \( f(x) = 3 - x \): \[ -x^2 + 5 = 3 - x \implies -x^2 + x + 2 = 0. \] Factoring gives \( (x-2)(x+1)=0 \), yielding \( x = 2 \) and \( x = -1 \). Substituting these \( x \)-values back to get \( y \)-coordinates: - For \( x = 2 \): \( y = 3 - 2 = 1 \) so \( (2, 1) \). - For \( x = -1 \): \( y = 3 - (-1) = 4 \) so \( (-1, 4) \). The points of intersection are \( (2, 1) \) and \( (-1, 4) \).

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy